IPO in family business: A systematic review and directions for future research. Issue 1 (March 2022) - Carbone, Emmadonata; Cirillo, Alessandro; Saggese, Sara; Sarto, Fabrizia
Highlights: The study offers a systematic literature review on IPO and family business papers published from 1995 to 2020. Ex-ante researches are organized on a theoretical model that roots on three phases of the going public transition. Results are analyzed throughout four levels: firm, family, individual and contextual. The paper suggests specific future research avenues and research questions to address with the most suitable methodology. Abstract: The transition from private to public ownership through the process of going public (i.e. initial public offering, or IPO) has attracted scholarly attention because of the governance, strategic and financial challenges and changes that firms face to achieve favourable valuations from equity markets. This is especially true for family companies, resulting in growing interest in the subject from family business scholars. This study systematically reviews existing research on IPOs in family businesses and assesses the state of the art in this field. It examines scholarly articles published in academic peer-reviewed journals from 1995 to 2020 and identifies research streams on the topic. It then systematizes the existing knowledge on IPOs in family firms through an input–process–output model that conceptually overlaps with IPO phases. This organizes the papers under investigation across four levels of analysis (firm, family, individual, and contextual levels). The article contributes to both research and practice by providing a useful theoretical driven model to guide future research efforts on IPOs in family businesses and suggesting specific policy interventions to support the listing process of family firms.